Oryctes rhinoceros beetles, an oil palm pest in Malaysia - Gnanasegaram, Manjeri; Muhamad, Rita; Tan, Soon Guan (Sciencedomain International, 2014)
Oryctes rhinoceros, commonly known as the rhinoceros beetle is an important agricultural pest that is known to inflict serious damage on young oil palm trees. Many researches have been conducted on its development, life cycle, habitat, management and genomic variation ever since the need to understand this pest arose. Oryctes rhinoceros is among the longest present agricultural pest in Malaysia and it has witnessed the formulation and implementation of various phases of control and management strategies. To date, research and development activities are still ongoing in Malaysia for the successful management of this pest. In this review, we look into details on the characteristics of this pest, the modes of its introduction into Malaysia, as well as the events that helped to establish and contribute to the proliferation of this pest as a major oil palm threat in Malaysia. The progressive development of various research and development activities concerning the management and control of this pest are also highlighted.